Easement procedure and factors which defined it in Ukraine - Lytvynenko, Iryna (KNUCA, 2015)
In the article various factors defining procedure of a land easement establishment when forming the new land plots are analyzed.All factors are combined into 4 groups. The analysis of influence of each group of factors on a land easement procedure in Ukraine is made.
Факторы, влияющие на процедуру установления земельных сервитутов в Украине
Keywords: right-of-way; utility; easement; easement procedure; easement establishment; factors; право прохода и проезда; инженерные коммуникации; сервитут; установление сервитута; факторы